TINGKAT KESEJAHTERAAN ORANGUTAN (Pongo spp.) DALAM KONSERVASI EX-SITUDI KEBUN BINATANG KASANG KULIM KECAMATAN SIAK HULU KABUPATEN KAMPAR RIAU - Kukuh Kurniawan; Defri Yoza; Viny Volcherina Darlis (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Orangutancan be used as one of the most unique primate species in Indonesia. The shrinking and destruction of lowland forest, which is the habitat for orangutan has now reached a critical point. Forest fires and rampant poaching have caused the orangutanpopulation to decline. The formulation of an orangutanconservation strategy is necessary to preserve the orangutan population. One of the efforts to prevent the extinction of endangered species is to maintain natural individuals under controlled conditions and under human supervision, known as ex-situ conservation. The purpose of this study was to determine the level of orangutan welfare in ex-situ conservation at Kasang Kulim Zoo. The welfare level oforangutan inex-situconservation at Kasang Kulim Zoo got a good predicate with a final score was 78.35. The aspects of orangutanwelfare include being free from hunger and thirst, free from environmental discomfort, free from pain, injury and disease, free from fear and pressure and free from behaving normally.Keywords :Orangutan, ex-situ conservation, intensity, prosperity level